2019
DOI: 10.1016/j.devcel.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

p120ctn-Mediated Organ Patterning Precedes and Determines Pancreatic Progenitor Fate

Abstract: Graphical Abstract Highlights d p120ctn expression segregates pancreatic progenitors into fate determining niches d p120ctn-low progenitors segregate into peripheral domains and form pro-acinar tips d p120ctn-high progenitors remain in the trunk to become duct and endocrine cells d p120ctn downregulation in endocrine cells drives delamination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…With our approach using zebrafish larvae, it is possible to visualize not only the whole endocrine cell population in relation to the ductal progenitor compartment, but also the morphology of single endocrine cells in 3D. Consistent with observations from explant studies showing that beta cells produce cytoplasmic protrusions and move along the duct to join other beta cells (Nyeng et al, 2019), our studies revealed that endocrine cells stay in proximity to the duct, and use dynamic protrusions to initiate cell-cell contacts which appear to direct cell coalescence.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…With our approach using zebrafish larvae, it is possible to visualize not only the whole endocrine cell population in relation to the ductal progenitor compartment, but also the morphology of single endocrine cells in 3D. Consistent with observations from explant studies showing that beta cells produce cytoplasmic protrusions and move along the duct to join other beta cells (Nyeng et al, 2019), our studies revealed that endocrine cells stay in proximity to the duct, and use dynamic protrusions to initiate cell-cell contacts which appear to direct cell coalescence.…”
Section: Discussionsupporting
confidence: 77%
“…The membrane targeted memKate co-localized with EGFP in the principal and secondary islets. In loosely associated secondary islet cells, the memKate highlighted cell contours as well as protrusions and fine cell-cell connections ( Figures 2I,J, arrows), which are proposed to play a functional role in the assembly process (Freudenblum et al, 2018;Nyeng et al, 2019).…”
Section: A Tool For Highlighting Cell Morphology During Islet Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…These clusters represent distinct pancreatic lineages at different embryonic stages, when the pancreatic epithelium is composed of MPCs. The MPCs undergo step-wise lineage restrictions and segregation into two distinct tip and trunk domains, which further differentiate into acinar and duct/EPs, respectively (Nyeng et al, 2019;Zhou et al, 2007). EPs then differentiate into Fev high cells that subsequently generate different types of endocrine hormone + cells (Fig.…”
Section: Single Cell Rna-seq Of the Embryonic Ep-enriched Pancreatic mentioning
confidence: 99%
“…From the analysis of clones traced from E12.5 to E14.5, E12.5 to E15.5 and E12.5 to E18.5, combined with insulin/DBA and glucagon/DBA immunostaining, we did not observe insulin+ or glucagon+ cell-contributing clones in PDE or ducts (Supplementary Fig. 2l–r ), although PDE localisation and endocrine lineage segregation might be temporally correlated 33 ).…”
Section: Resultsmentioning
confidence: 86%